STUDENTS’ ATTITUDE TOWARDS ENGLISH LANGUAGE LEARNING: A STUDY OF YEAR 9TH STUDENTS OF SMPN 3 LABAKKANG - Gunawan, Hendra; Korompot, Chairil Anwar; Tahir, Muh. (Universitas Negeri Makassar, 2023)
This study aims to determine the attitude of the 9th grade students of SMPN 3 Labakkang towards learning English. This study used a mix-method. The variables in this study were English and students' attitudes. The instruments used are questionnaires and interviews. The subjects of this study were year 9th students and English teachers at SMPN 3 Labakkang for the academic year 2022/2023. Sample The questionnaire collected 25 students, and interviewed 5 students and 2 English teachers who were selected through simple random sampling. The results of the questionnaire data analysis showed that students had a relatively positive attitude, with the classification of 14 (56%) students being classified as positive attitude, 8 (32%) students being classified as neutral attitude, and 3 (12%) students being classified as negative attitude. The overall explanation in the interview stated that the students' attitudes that emerged when learning English tended to be positive attitudes and the teacher's perception of these students' attitudes to form students' positive attitudes, it was necessary to apply good teaching techniques and fun materials.